1964
DOI: 10.1071/ph640462
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Townsend's Energy Factor k1 for Electrons in Carbon Dioxide

Abstract: SummaryValues of Townsend's energy factor kl for electrons in carbon dioxide have been determined as a function of the parameter E/p for 0·1 .;;; E/p .;;; 50 at a temperature of 293°K. The results are compared with those of other investigators and are used in a recomparison of the cross sections for electron attachment deduced from swarm and beam types of experiments for swarms of electrons having mean energies of up to 5 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

1965
1965
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
2
8
1
Order By: Relevance
“…Although the results of a number of workers (Townsend and Bailey 1921;Crompton and Sutton 1952;Cochran and Forester 1962;Warren and Parker 1962;Rees 1964;Rees and Jory 1(64) are in reasonable agreement when the mean energy of the electron swarm is in excess of about 0·5 e V, the agreement is not satisfactory when the electron energy approaches the energy of the gas molecules. Our own experience and that of Warren and Parker (1962) have shown that considerable difficulties exist in obtaining reliable, and therefore significant, data in this low energy region.…”
Section: (I)mentioning
confidence: 84%
“…Although the results of a number of workers (Townsend and Bailey 1921;Crompton and Sutton 1952;Cochran and Forester 1962;Warren and Parker 1962;Rees 1964;Rees and Jory 1(64) are in reasonable agreement when the mean energy of the electron swarm is in excess of about 0·5 e V, the agreement is not satisfactory when the electron energy approaches the energy of the gas molecules. Our own experience and that of Warren and Parker (1962) have shown that considerable difficulties exist in obtaining reliable, and therefore significant, data in this low energy region.…”
Section: (I)mentioning
confidence: 84%
“…Figure 4 shows such a comparison between Buchel'nikova's data and the data from our experiments where the data have been analysed on the basis of a Maxwellian distribution, using the values of kl given in Table 1 * The values of c1a computed from data for aa/P for dry air and carbon dioxide by Rees (1964) and Rees and Jory (1964) are in error by 7%, the correct values being 7% higher than those quoted. This systematic error does not in any way affect the conclusions drawn from the compari- from a recalculation of these data using the newer data for kl and W is also shown.…”
Section: (4)mentioning
confidence: 91%
“…Prasad and Craggs 1961;Rees 1964;Rees and Jory 1964) have shown discrepancies no greater than might be expected as a result of imprecise knowledge of the appropriate energy distributions, the comparisons for water vapour (Prasad and Craggs 1960) were a notable exception. For this gas, values of ua calculated from swarm experiments exceeded the corresponding values calculated from Buchel'nikova's data by a factor of 5 in some instances.…”
Section: Comparison Of Attachment Data From Beam and Swarm Experimentioning
confidence: 99%
See 1 more Smart Citation
“…1·2 3·64 6·533 6·539 6·536 6'536 1·0 3·03 5·421 5·425 5·421 5'421 0·9 2·73 4·869 4·865 4·871 4'868 0·8 2·43 4·322 4·327 4·322 4'32, 0·7 2·124 3·780 3·785 3'783 3·786 3'78, 0·6 1·820 3·236 3·240 3·245 3·244 3.24 1 0·5 1·517 2·698 2·700 2·699 2·704 2'700 0·4 1·214 2·158 2·158 2·162 2·162 2.16 0 0·3 0·910 1·621 1·620 1·621 1·621 0·25 0·759 1·350 1·351 1·352 1·351 0·2 0·607 1·080 1·081 1·081 0·18 0·546 0·972 0·972 0·972 0·15 0·455 0'811 0·811 0·811 0·12 0·364 0·649 0·651 0·650 0·1 0·303 0·541 0·541 The error has been calculated for all values of E /P293 and E used in the present measurements, using the values of W/pD measured by Rees (1964). With the exception of the values at E /p = 6 and 7, the maximum difference between W a.nd W' is less tha.n 0·2%.…”
Section: Resultsmentioning
confidence: 99%